Compact, gain-enhanced 5G mmWave antenna with metallic ground-backed reflector for high-speed railway communication systems - Mohammed, Dunya Zeki; Al Gburi, Ahmed Jamal Abdullah (Elsevier B.V., 2025)
This research presents a compact, high-gain millimeter-wave antenna tailored for reliable 5 G communication in high-speed railway environments. The proposed antenna supports dual-band operation at 28 GHz (n257/n258) and 38 GHz (n260), enabling robust Vehicle-to-Infrastructure (V2I) links required for next-generation railway systems. The radiator occupies only 12 mm × 8 mm on a Rogers 6010LM substrate (εᵣ = 10.2, h = 0.64 mm). A Metallic Ground-Backing (MGB) reflector, positioned 9 mm behind the patch—λ/4 at 28 GHz—enhances forward radiation, suppresses back-lobes, and ensures highly directional coverage along railway tracks. The antenna achieves measured peak gains of 7.96 dBi at 28 GHz and 8.20 dBi at 38 GHz, with excellent impedance matching and stable radiation patterns under mobility scenarios. Its unique combination of compact footprint, reflectoraided gain enhancement, and stable dual-band performance under dynamic conditions distinguishes it from conventional millimeter-wave solutions, making it a strong candidate for 5G-based high-speed railway communication modules and arrays.